Association Between Pediatric Sofa Score and Coagulation Abnormalities in Critically Ill Children at Dr. Soetomo General Hospital: A Retrospective Study - Saskia Putri Fadillah; Arina Setyaningtyas; Pradana Zaky Romadhon; Bambang Pujo Semedi (Indonesian Journal of Anesthesiology and Reanimation, 2026)
Introduction: Coagulation disorder is a common complication related to mortality in pediatric patients at the intensive care unit. It is characterized by prolongation of blood clotting time as reflected in activated partial thromboplastin time (APTT) and prothrombin time (PT) values. Organ dysfunction, often found in a patient with critical illness, is one of the causes of coagulation disorder. The degree of organ dysfunction in pediatric patients can be assessed using the pediatric sequential organ failure assessment (pSOFA) score. Objective: To analyze the association of pSOFA score with coagulation disorder and the association of thrombocytopenia with mortality in critically ill children at the PICU. Methods: This study used a retrospective analytical observational design involving 43 critically ill pediatric patients with organ dysfunction treated in the PICU of Dr. Soetomo General Hospital in 2023. The associations between pSOFA score and coagulation parameters, as well as thrombocytopenia and mortality, were statistically analyzed using the chi-square test. The pSOFA cutoff value for predicting coagulation disorder was determined by the ROC curve. Results: The pSOFA score was significantly associated with prolonged APTT (p= <0.001; φ= 0.506) and PT (p= 0.018; φ= 0.362). The cutoff point of a pSOFA score ≥6.5 for APTT prolongation showed 86.7% sensitivity and 71.4% specificity (AUC= 0.804). With a pSOFA score cutoff point of ≥8.5 for PT prolongation, the sensitivity was 56.3% and the specificity was 85.2% (AUC= 0.720). Subanalysis showed a significant association between thrombocytopenia and mortality (p= 0.017; φ= 0.365). Conclusions: The pSOFA score was significantly associated with APTT and PT prolongation, and thrombocytopenia was significantly associated with mortality in critically ill children.